Educational psychology - Tuckman, Bruce W.; Monetti, David M. (Wadsworth/Cengage Learning, 2011)
This comprehensive educational psychology text blends a strong scholarly and theoretical background with the application of theories and concepts using real-world examples, case studies, and practical teaching strategies. The text's innovative pedagogical program is anchored by a cohesive learning objective system integrated throughout each chapter, guiding students' reading and reinforcing their understanding of concepts. A unique Think It Over feature asks readers to reflect on important topics as both a student of psychology and a future classroom teacher. TeachSource Video Cases, introduced in the text and available to view on the book's Companion Website, give students a firsthand look at real-world applications and best practices. Among the other distinctive aspects of the text is an entire chapter on group process.